Mentoring dan Dukungan Sosial Terhadap Minat Berwirausaha Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Negeri Padang - Nurhaliza, Putri; Murdy, Khairi (Jurnal E-Bis, 2025)
This study aims to analyze the influence of mentoring and social support on the entrepreneurial interest of students at the Faculty of Economics and Business, Universitas Negeri Padang. The research employed a quantitative associative approach. The population included active students who had completed the Entrepreneurship Practice course. The sample was selected using purposive random sampling. Data were collected using questionnaires with a Likert scale. The results indicate that mentoring and social support have a positive and significant impact on students’ entrepreneurial interest, both individually and simultaneously. Mentoring provides direction and practical experience, enhancing students' interest in entrepreneurship, while social support from family, peers, and lecturers increases confidence and motivation. The study concludes that the combination of mentoring and social support plays a crucial role in fostering the entrepreneurial spirit among students.